(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The process of separation of proline from accompanying amino-acids of the proline cultural liquid on anion exchange resin has been investigated and it was shown that the division takes place effectively on strong base anionite. The process of decoloration and desalting of eluat of amino-acids mixture on cation exchange resin has been studied and the optimal parameters have been defined. The coefficients of amino-acids distribution from decoloured and desalted eluat on AV-17 anionite at the OH -form in static conditions has been defined and it was shown that proline has the smallest selectivity to anionite, while isoleucine has the greatest one. In the dynamic conditions amino-acids sorption curves on AV-17 anionite have been obtained and the optimal technological parameters of the process of separation of proline from amino-acid have been defined.